Severe acute respiratory syndrome coronavirus 2: a canary in the coal mine for public safety net hospitalsAJOG MFM at a Glance - Crista E. Johnson-Agbakwu, MD, MSc; Cortney M. Eakin, MD; Celeste V. Bailey, MD; Shelly Sood, MD; Nyima Ali, MD; Pooja Doehrman, MD, MPH; Bikash Bhattarai, PhD; Linda Chambliss, MD; Dean V. Coonrod, MD, MPH (Elsevier, 2021)
BACKGROUND: The coronavirus disease 2019 pandemic has exposed disproportionate health inequities among underserved populations, including refugees. Public safety net healthcare systems play a critical role in facilitating access to care for refugees and informing coordinated public health prevention and mitigation efforts during a pandemic. OBJECTIVE: This study aimed to evaluate the prevalence ratios of severe acute respiratory syndrome coronavirus 2 infection between refugee women and nonrefugee parturient patients admitted to the hospital for delivery. Here, we suspected that the burden of infection was disproportionately distributed across refugee communities that may act as sentinels for community outbreaks. STUDY DESIGN: A cross-sectional study was conducted examining parturient women admitted to the maternity unit between May 6, 2020, and July 22, 2020, when universal testing for severe acute respiratory syndrome coronavirus 2 was first employed. Risk factors for severe acute respiratory syndrome 2 positivity were ascertained, disaggregated by refugee status, and other clinical and sociodemographic variables examined. Prevalence ratios were calculated and comparisons made to county-level community prevalence over the same period. RESULTS: The positive test percentage at the county-level during this study period was 21.6%. Of 350 women admitted to the hospital for delivery, 33 (9.4%) tested positive for severe acute respiratory syndrome 2. When refugee status was determined, 45 women (12.8%) were identified as refugees. Of the 45 refugee women, 8 (17.8%) tested positive for severe acute respiratory syndrome 2 compared with 25 nonrefugee patients (8.19%) who tested positive for severe acute respiratory syndrome 2 (prevalence ratio, 2.16; 95% confidence interval, 1.04-4.51). In addition, 7 of the refugee women who tested positive for severe acute respiratory syndrome coronavirus 2 were from Central Africa. CONCLUSION: The severe acute respiratory syndrome coronavirus 2 outbreak has disproportionately affected refugee populations. This study highlighted the utility of universal screening in mounting a rapid response to an evolving pandemic and how we can better serve refugee communities. Focused response may help achieve more equitable care related to severe acute respiratory syndrome 2 among vulnerable communities. The identification of such populations may help mitigate the spread of the disease and facilitate a timely, culturally, and linguistically enhanced public health response.